Inovasi Pengolahan Limbah Biji Alpukat Menjadi Produk Teh Herbal Berbasis Pemberdayaan Masyarakat Desa di Desa Bebidas Lombok Timur - Mia Tri Ardene; Nadiatul Aini; Adittya Abdilah; Alif Rizqian Maulana Al Jufri; Alya Zahra Satriani; Dwy Anggriani; Muh. Tanwir; Nindia Salsabila; Nurul Falahtunnisa; Yusfita Yusfita; Heri Setiawan (Educational Consultant & Counseling Career (EC3) Mataram, 2026)
Bebidas Village, Wanasaba District, East Lombok Regency has the potential for abundant natural products in the form of avocados, but its use is still limited to sales in raw form so that the added value obtained by the community is relatively low. One of the waste that has not been optimally utilized is avocado seeds, even though this part contains bioactive compounds that have the potential to be developed into herbal products. This activity aims to improve the knowledge and skills of the community in processing avocado seed waste into herbal tea products with economic value through a community empowerment approach. The implementation method includes problem identification, socialization, appropriate technology-based processing training, and assistance in the production process and product diversification with original, honey, and lemon flavor variants. The targets of the activity are PKK groups, youth, MSME actors, and the people of Bebidas Village. The results of the activity show an increase in public understanding of the benefits of avocado seeds, technical capabilities in the post-harvest processing process, and the emergence of interest in developing products as a household business. This activity contributes to reducing organic waste, increasing the added value of local commodities, and strengthening the village economy based on the potential of natural resources.